Use of Metallographic Analysis for Evaluating Microstructures in Quenched and Tempered High-Strength Steel - Janda, Tomas (Manufacturing Technology Journal, 2018)
The experiment described herein focused on quantitative evaluation of carbides in the martensitic microstructure of X105CrMo17 steel. Carbides form as a result of the varying solubility of carbon and alloying elements during solidification and cooling. They possess high strength and hardness and their morphology plays a major role in mechanical properties of steel. In order to determine the relationship between carbide morphology and mechanical properties, several characteristics must be measured accurately. In this case, quantitative evaluation of carbides by means of optical microscopy and image analysis software were employed. Samples of the above-identified steel were quenched from various temperatures in order to obtain various levels of chromium and carbon dissolved in the martensitic matrix. They were then tempered at various temperatures to provide secondary hardening through precipitation. Furthermore, volume fractions and equivalent diameters of particles and the surface area density of particles were measured by metallographic techniques. Hardness was measured to assess the impact of heat treatment on strength. From the values collected in this manner, relationships between heat treatment and hardness were derived and an optimal heat treatment sequence was proposed for obtaining maximum hardness.
Keywords: High-strength steel; heat treatment; quantitative metallography; precipitation hardening